Development And Optimization Of Wireless Charging System For Electric Vehicle (EV) - Chong, Wei You (2020)
Wireless charging for electric vehicle (EV) was an innovative invention as it did not need a direct connection or contact between vehicle and the charging cable. The owner of the wireless charging electric vehicle just have to park their vehicles just above the transmitter charging pad within the acceptable lateral range between the transmitter and receiver pad beneath the electric vehicle. The objectives of this project were to study the wireless charging system of electric vehicle, design and optimize the system in terms of coil alignment, compensation circuit and coil design to solve the issues of power loss and improving charging rate when charging the electric car. The methodology was the power source is direct from wall socket that provides 240Vac with 50Hz. The AC current was rectified and inverted back to produce higher frequency AC current up to 20kHz. The coil design was in spiral flat circular shape to ensure the magnetic field produced was evenly distributed. For the alignment system, mechanical aligner was constructed and communicate with mobile phone with the concept of Internet of Things (IoT). The results shown that the greater the misalignment, the lower the power efficiency, mutual inductance, and coupling coefficient verified using simulation software called Ansys Maxwell and SIMULINK. In conclusion, the project was conducted successfully as the results from simulation matched with the experimental results.